Deskripsi Kebutuhan Evaluasi Tes Matematika Melalui Pembelajaran Asinkron Berbasis LMS Moodle - Fhinanda Fhilo Sofhia; Nuryadi; Nafida Hetty Marhaeni (Jurnal Inovasi Pendidikan Matematika (JIPM), 2022)
Technological developments demand innovation in the implementation of education, one of which is the implementation of learning evaluation. Currently, learning evaluation can be done online through asynchronous learning. Asynchronous learning is student-centred because it can make students learn independently using the necessary online learning resources. For this reason, this study aims to describe the need for evaluating mathematics tests through asynchronous learning to improve student learning outcomes. The type of research used is descriptive qualitative. The population taken in this study were students of class X SMA in Yogyakarta, with a sample of class X IPA 3 of as many as 36 students taken by purposive sampling technique. Data collection techniques used interviews, preliminary study questionnaires, and the value of the end-of-semester assessment result. The results showed that as many as 16,67% of students' mathematics learning was still below the KKM, the implementation of mathematics tests had not been carried out using moodle-based asynchronous learning, and as many as 80% of students were interested in evaluation activities, or tests were carried out online through moodle-based asynchronous learning. The research shows that evaluating students’ mathematics tests through asynchronous learning needs to be applied to improve student learning outcomes.